2016
DOI: 10.1007/s11694-016-9339-7
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic extracts of carrot, grape leaf and turmeric powder: antioxidant potential and application in biscuits

Abstract: Natural antioxidants have gained interest for their role in preventing lipids oxidation. The goals of this investigation were to study the antioxidant potential of carrot (Daucus carota), grape (Vitis vinifera) leaf and turmeric (Curcuma longa) powder extracts and to evaluate their addition as natural antioxidants in biscuits. Physical and chemical properties of biscuit were evaluated during processing and storage. Electrophoretic properties of biscuit dough were carried out to understand the impact of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Hence, these results suggested that CIP can be effectively fought against DM. This action is principally due to the antioxidant potential of carrot [17] and incorporation of carrot juice to the paneer confirmed that the presence of antioxidants in CIP could involve a mechanism associated with scavenging activity to prevent DM.…”
Section: Resultsmentioning
confidence: 77%
“…Hence, these results suggested that CIP can be effectively fought against DM. This action is principally due to the antioxidant potential of carrot [17] and incorporation of carrot juice to the paneer confirmed that the presence of antioxidants in CIP could involve a mechanism associated with scavenging activity to prevent DM.…”
Section: Resultsmentioning
confidence: 77%
“…Applications of these natural antioxidants in biscuit formulations replacing synthetic antioxidants are gaining interest. Several natural extracts are reported to be used as a rich source of polyphenols such as Daucus carota (Hefnawy et al ., 2016), Armoracia rusticana L (Tamsone et al ., 2020), which are reported to be used in biscuit formulation. The solvent used for extraction of D. hamiltonii tuber extract has had a significant effect on the total concentration of polyphenols (Yang et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the addition of curcumin to the composite flour would enhance the functionality and nutritional composition of the baked food products. Curcuminrich turmeric (Curcuma longa) powder extracts were used as a natural antioxidant in the preparation of biscuits by Hefnawy et al (176) along with carrot (Daucus carota) and grape (Vitis vinifera) leaf. Besides this, turmeric from 1 to 5% was used to improve the color, increase the fiber content and increase the antioxidant properties of pasta while retaining the technological attributes (159).…”
Section: Cereal-based Productmentioning
confidence: 99%